Compulsão alimentar e fatores de estilo de vida em participantes do estudo ELSA Brasil - Silva, Thamyres Souza da (2014)
Binge-eating (BE) is a type of overeating disorder which can present as an isolate symptom or associated with other eating disorders. Such disorder is related to lifestyle, food consumption patterns and metabolic changes that may contribute to other health problems and hazards. The aim of this study was to investigate episodes of binge eating and its relationship with the nutritional, alimentary, and lifestyle profiles in a cohort from the Longitudinal Study of Adult Health (ELSA-Brazil). A cross-sectional study was conducted based on interviews made with 15,105 civil servants who constituted the primarily collected data of ELSA-Brazil in 2010. The outcome variable was the presence of an episode of binge eating assessed by interview using the DSM- IV. Exposure variables were constituted by socio-demographic (age, sex, race/color and education), alimentary (caloric value and by food groups), nutritional (body mass index), and lifestyle (smoking, alcohol, and physical activity) data. Dietary intake was grouped into quintiles and evaluated using ANOVA. Categorical variables were compared and a logistic regression was performed using the significant variables (p < 0,05). We found a 6.5% prevalence of COA episodes which were more frequent in women (66.6%), younger people (68.2%), Caucasian (45.6%), with higher education levels (47%), obese (45.9%), less active (64.6%), with increased caloric intake and consumption of large amount of alcohol in a short period of time. Binge-eating was associated with obesity (OR 5.188; CI 4.051 to 6.645), overweight (OR 2.534; CI 1.980 to 3.243), female sex (OR 1.918; CI 1.573 to 2.338), age of 34-54 years (OR 1.349; CI 1.115 to 1.631), alcohol intake ≥ five drinks in two hours (OR 1.397; CI 1.068 to 1.827), and insufficient physical activity (OR 1.290; CI 1.078 to 1.544). Consequently, it is possible to conclude that the overweight was a major determinant for BE, also suggesting that there are other patterns of compulsive behavior involved.